Effects of Filgrastim in Neonates Having Neonatal Sepsis and Neutropenia - Abdullah; Hasan, Brig Shamama; Taroni, Silwana; Nawaz, Wahid; Nawaz, Wahid; Habib, Kamran (Indus Journal of Bioscience Research, 2025)
Background: Neonatal sepsis with neutropenia is a critical condition that causes increased morbidity and mortality within 28 days of birth. Filgrastim acts by stimulating the bone marrow to increase neutrophils; however, its use in neonates with sepsis is not fully elucidated. Objective: To compare the effect of filgrastim plus conventional therapy versus conventional therapy alone on absolute neutrophil count in neonates having sepsis with neutropenia. Study Design: Randomized controlled trial. Duration and Place of Study: This study was conducted from 1 September 2024 to 1 March 2025 in Department of Pediatrics, Combined Military Hospital Rawalpindi. Methodology:  Total 60 neonates aged less than 28 days were included, with 30 in each group. Group A received filgrastim 10 microgram per kilogram per day for 3 days along with conventional therapy, while Group B received conventional therapy only. Absolute neutrophil count was measured at baseline and after 5 days. Data was analyzed using SPSS 23. Results: Baseline absolute neutrophil count was comparable in both groups (913.27 ± 302.00 per millimeter cube versus 871.47 ± 306.32 per millimeter cube). After 5 days, mean absolute neutrophil count was significantly higher in Group A (4872.00 ± 912.94 per millimeter cube) compared to Group B (4052.00 ± 1011.09 per millimeter cube) with p = 0.002. Significant improvement was also seen in neonates aged more than 14 days (p = 0.019), males (p = 0.009), birth weight more than 2.5 kilogram (p = 0.004) and cesarean delivery (p = 0.008). Conclusion: Filgrastim added with conventional therapy significantly improves absolute neutrophil count in neonates having sepsis with neutropenia.